Anaerobic capacity estimated by a single effort distinguishes training status in male cyclists - Dutra, Yago Medeiros [UNESP] (2020)
Background: Measurement of anaerobic capacity through estimating the glycolytic and phosphagen energy pathways (AC[La]+PCr) has been considered a time-efficient, valid, and reproducible method, however, the sensitivity of this protocol to discriminate training levels in cyclists has not yet been elucidated. Aims: The main purpose of the present investigation was to verify the sensitivity of AC[La]+PCr to distinguish the anaerobic capacity of male cyclists with different training status. Methods: Fifty-five healthy men performed a maximum incremental test to determine maximal oxygen uptake (V ˙ O 2max) and the intensity associated with it (iV ˙ O 2max) , and a constant-load supramaximal-intensity cycling exercise at 115% of the iV ˙ O 2max to determine anaerobic capacity through AC[La]+PCr. Results: According to performance in the incremental test, 20 subjects were classified as untrained (V ˙ O 2max = 2.92 ± 0.28 L min−1), 25 classified as recreationally trained (V ˙ O 2max3.78 ± 0.19 L min−1), and 10 classified as trained (V ˙ O 2max = 4.36 ± 0.41 L min−1). Expressed in absolute values, the trained group presented higher anaerobic capacity measured through AC[La]+PCr [4.82 ± 1.07 L (4.05–5.59 L)] than the recreationally trained [4.13 ± 0.64 L (3.87–4.4 L)] (p = 0.027) and untrained groups [3.22 ± 0.42 L (3.02–3.42 L)] (p = 0.001). In addition, the recreationally trained group also demonstrated significantly higher anaerobic capacity values than the untrained group (p = 0.001). Conclusion: The AC[La]+PCr was sensitive to discriminate the anaerobic capacity between trained, recreationally trained, and untrained male cyclists.